Innovative analysis in climate change: Evidence from developed European countries - Barykin, Sergey; Yadykin, Vladimir; Badenko, Vladimir; Sergeev, Sergey; Bezborodov, Andrey; Lavskaya, Kristina; Poza, Elena de la; Morkovkin, Dmitry; Shchukina, Tatyana; Veynberg, Roman; Rassylnikov, Igor; Svechnikova, Vera; et al. (Frontiers in Environmental Science, 2022)
Since the turn of the 20th century, the whole world entered a period of technological singularity. It is also predicted that the pace of innovation regarding problems associated with climate change, generational change of technologies will constantly increase. This paper aims to bring an innovative product to the market regarding subsequent economical and social strategy. The methodology is based on a dynamic assessment of the development of consumer demand in the context of innovative proposals. In the article, results are obtained and the volume of investments in the development of innovations is determined, which optimizes the balance between curtailing the volume of output using the previous technology in climate change and increasing the production and sale of an innovative product in climate change. The novelty of this study is in the panel framework on the base of Model Based System Engineering (MBSE). The study concludes that MBSE are more sensitive to innovative activity. The volume of investments in the development of innovations is determined. The main result is the total profit from the demand in the consumer market for products based on old and new technologies in climate change, since reformed business processes entail significant financial costs. The above-discussed issues lead to inappropriate misleading policy recommendations. The main recommendation is using disaggregated trade data for each trading partner and industry level to conclude more accurate results and policy recommendations for each trading partner and industry in concern.